Elucidating the prognostic significance of KRAS, NRAS, BRAF and PIK3CA mutations in Chinese patients with metastatic colorectal cancer. Issue 2 (13th April 2015) - Ma, Brigette B; Mo, Frankie; Tong, Joanna H; Wong, Ashley; Wong, SC Cesar; Ho, Wing M; Wu, Cherry; Lam, Polly WY; Chan, KF; Chan, Timothy SK; Tsui, Wilson MS; Tsang, Alex KH; et al.
Abstract Aim The prognostic significance of KRAS, NRAS, PIK3CA and BRAF mutations was evaluated in Chinese patients with metastatic colorectal cancer (CRC). Method Tumor samples from 183 patients were retrospectively tested for KRAS, NRAS, PIK3CA and BRAF mutations. Multivariate analysis was performed to determine the relationship between mutational status, drug response and survival. Result Over 70% of patients received two or more lines of chemotherapy, 50% had cetuximab and 18% had bevacizumab. The prevalence of KRAS, NRAS, BRAF and PIK3CA mutations was 45, 3.2, 5 and 20%, respectively. For the entire cohort, the median overall survival was 24 months (95% confidence interval [CI] = 20.4–26.4 months). Of the genes tested, only KRAS mutation was an independent prognostic factor with a multivariate hazard ratio of 1.5 (95% CI = 1.05–2.16, P = 0.03). In the subgroup of patients who received cetuximab‐based therapy in the first‐line setting, KRAS mutation was associated with a lack of response to chemotherapy (28% vs 66%, chi‐square, P = 0.01). Patients with KRAS mutant tumors (or KRAS wild‐type tumors that harbored BRAF and/or PIK3CA mutations) tended to have lower response rates to chemotherapy and/or cetuximab (P = not significant). The number of NRAS mutant cases was too small to allow any statistical analysis. Conclusion The prevalence of KRAS, NRAS, BRAF and PIK3CA mutations in this cohort is consistent with reports from non‐Asian populations, and KRAS mutation has both prognostic and predictive significance in Chinese patients with metastatic CRC.